Survival of Trichinella spiralis and T. pseudospiralis in Experimentally Infected Wild Boar Muscle Tissue under Freezing and Environmental Conditions - Bessi, Clara (2024)
Background: The aim of this study was to investigate the survival of Trichinella spiralis and T. pseudospiralis in decaying wild boar tissue and assess their freezing tolerance in experimentally infected animals.Methods: The present study was conducted in Buenos Aires City, Argentina during the 2018-2019 period. Two wild boars were used, one infected with 20,000 muscle larvae (ML) of T. spiralis and the other with T. pseudospiralis. Both animals were euthanized 19 weeks post-infection. Limbs from each boar were placed over soil in plastic containers to assess ML survival in decaying tissue, under natural temperature and humidity, shielded from rain. Weekly samples were taken for artificial digestion, and the ML were inoculated into mice to determine their reproductive capacity index (RCI). Additionally, to evaluate the freezing tolerance of the ML, muscle samples were stored at -18°C. Six samples were taken and digested after 2, 4, 7, 9, 11, and 14 days, with subsequent inoculation into mice to assess RCI. Results: T. spiralis remained infective in decaying wild boar tissue for 11 weeks, while T. pseudospiralis remained infective for only 4 weeks. The freezing tolerance assay showed that T. spiralis ML remain infective for 9 days. However, T. pseudospiralis ML remain infective for only 2 days at -18°C.Conclusion: The findings highlight the survival strategies of T. spiralis and T. pseudospiralis in different environmental conditions, which may have implications for understanding their transmission dynamics in wild animals.